Construction History (JSTOR)
Construction History, the journal of the Construction History Society, is a peer-reviewed scholarly journal which is published annually. It is the leading international journal in its field, and enjoys a high reputation in the diversity, breadth and detail of its coverage. The journal covers all aspects of construction history and recent papers have ranged from buildings in early China to construction processes in the modern USA, and from nineteenth century British bridge building to the use of concrete in India and Mexico. The scope embraces both technical and non-technical aspects of construction history. Among technical issues covered in Construction History are construction materials and components, buildings, infrastructure, building form, construction processes and plant. Non-technical aspects of construction include funding, organisations, company history, labour, education and historical sources. The journal does not include papers about the refurbishment of existing buildings or engineering structures. Each volume of around 150 pages contains up to six or seven generously illustrated papers by authoritative writers. Each volume also contains informative abstracts of papers in periodicals and other literature. Future volumes will also include a list of recent book titles.
Keywords: Architecture & Architectural History